Quality Analysis of E-government Services Using SERVQUAL Method (Case Study of SAMSAT Office in Kolaka Regency) - Ningsi, Nurfitria; Z, Noorhasanah; Gusnawati, Gusnawati (Universitas Nusantara PGRI Kediri, 2020)
This study discusses the measurement of the quality of motor vehicle tax of information system services at the SAMSAT Kolaka office using the servqual method by emphasizing the five dimensions of servqual namely Tangibles, Reliability, Responsiveness, Assurance and empathy. This study aims to understand the level of user satisfaction by comparing expectations and expectations and updating the standards provided by SAMSAT Kolaka through the application of the SIZ application. Data collection activities were carried out by distributing 100 questionnaires to all SIZ service users. The results of this study indicate that the use of SIZ is not by customer needs; this can be demonstrated by the high value of the gap between expectations and perceptions. The Assurance dimension obtaining the most top difference is the Tangibles dimension indicating that the limitations of the IT facilities used are still limited. It is evidenced by the continued complaints of customers regarding queue buildup due to a system that suddenly goes down while the service is in progress. It is necessary to improve IT infrastructure that can improve customer satisfaction in the future.